2021
DOI: 10.1002/nav.22014
|View full text |Cite
|
Sign up to set email alerts
|

Duopolistic positioning and pricing competition with variety‐seeking and strategic consumers

Abstract: This paper examines a duopolistic market in which two firms compete on their positioning and pricing decisions. Consumers may be variety-seeking or non-variety-seeking, and strategic or myopic, in their repeated purchases. The competing firms first determine the positioning and then the prices in two selling periods under either price commitment or dynamic pricing. Contrary to the conventional wisdom that variety-seeking consumers are less profitable consumers, we find that firms may benefit from more variety-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Second, we further compare symmetric firms' equilibrium prices and profits under both committed and dynamic pricing schemes. When the strength of the spillover effect is large compared to the competition intensity level, committed pricing can help alleviate the price competition, and benefit the firms more than dynamic pricing does, which is consistent with the existing literature (Liu & Zhang, 2013; Shang et al, 2021; Wang & Hu, 2014). By contrast, when the quality spillover is weak, dynamic pricing scheme brings more profits for the duopoly, as firms can take advantage of the pricing flexibility and earn a high second‐period profit without sacrificing the first‐period profit for self quality improvement.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Second, we further compare symmetric firms' equilibrium prices and profits under both committed and dynamic pricing schemes. When the strength of the spillover effect is large compared to the competition intensity level, committed pricing can help alleviate the price competition, and benefit the firms more than dynamic pricing does, which is consistent with the existing literature (Liu & Zhang, 2013; Shang et al, 2021; Wang & Hu, 2014). By contrast, when the quality spillover is weak, dynamic pricing scheme brings more profits for the duopoly, as firms can take advantage of the pricing flexibility and earn a high second‐period profit without sacrificing the first‐period profit for self quality improvement.…”
Section: Introductionsupporting
confidence: 88%
“…For example, dynamic pricing allows firms to make inter‐temporal changes to the posted price so that it is contingent to the evolving environment; committed pricing, on the other hand, could generally relax the competition and is relatively easy to implement. Depending on the practical situation, one strategy may outperform the other, as shown in several prior works in economics and operation management literature (Liu & Zhang, 2013; Shang et al, 2021; Wang & Hu, 2014). Here, we compare the duopoly pricing game under these two pricing schemes in the presence of the learning and quality improvement spillover.…”
Section: The Two‐period Model With Symmetric Firmsmentioning
confidence: 98%
See 2 more Smart Citations
“…Lin et al [31] found that manufacturers and retailers earn higher profts in the presence of strategic consumers in the view of holistic supply chain. In terms of recent pricing research considering strategic consumers, it has begun to capture the characteristics of supply chains under complex consumption scenarios, for instance, segmented market such as sharing economy [11] and low-carbon products [32], two-echelon newsvendor [33], purchase behaviors including repeat purchasing [34], defective product returns [12], and so forth. Tere are related articles exploring strategic consumers' impact in channel selection.…”
Section: Literature Reviewmentioning
confidence: 99%